Aetiology and risk factors associated with septicaemia of dogs in Malaysia - Rathiymaler, M.; Salleh, Annas; Saad, Mohd Zamri; Abdullah, Faez Firdaus Jesse; Zakaria, Zunita (Medwell Online, 2017)
Septicaemia is an important health problem in both veterinary and human medicines. This study reports on the aetiology and risks of septicaemia in dogs submitted to the Post-mortem Laboratory, Faculty of Veterinary Medicine, Universiti Putra Malaysia between 2006-2016. It was found that the most common point of entry of microorganisms leading to septicaemia in dogs was via the gastrointestinal tract (57%, p<0.05). Commonly isolated aetiological agents were Escherichia coli (65%), Streptococcus sp. (15%), Staphylococcus sp. (12%), Klebsiella pneumoniae (3%), Pasteurella sp. (2.5%) and Salmonella sp. (2.5%). The septicaemia was associated with risk factors which included underlying infection (60.8%), stress (36.7%), malnutrition (21.7%), tumor (7.5%) and traumatic mjury (5%). Analysis of association between age group and risk factors showed that pediatrics were very susceptible and this was closely associated with underlying viral infection. Other important risk factors included injury to the integument and malnutrition. Reasons behind these observations were subsequently discussed.